Education on Physical Activity Patterns and Healthy Diets to Manage Blood Sugar Levels in Diabetes Mellitus Patients - Iis Fatimawati; Hanum Maulina; Diyah Arini; Dwi Ernawati; Astrida Budiarti (Jurnal Penelitian Pendidikan IPA, 2026)
This study analyzed the relationship between physical activity, diet, and blood sugar levels in patients with diabetes mellitus at the Tambak Wedi Baru Community Health Center, Surabaya, from February to May 2025. The study design used was a correlational analytic design with a cross-sectional approach. The sample consisted of 72 respondents aged 20 to 71 years, who were selected randomly. Univariate analysis focused on a single variable through descriptive statistics, presenting data as numbers, ratios, percentages, or prevalence. Bivariate analysis examined the relationship between two variables using non-parametric statistics, such as the Spearman test, to explore associations between diet, physical activity, and blood sugar levels. Findings revealed significant relationships between physical activity and diet and blood sugar levels (ρ = 0.007; ρ = 0.000). Good physical activity (>1500 MET-min) was associated with normal blood sugar levels, while low physical activity (<600 MET-min) was associated with abnormal blood sugar levels. On the other hand, poor diet (<650 calories) also contributed to high blood sugar levels. This study highlights the importance of multidisciplinary interventions to increase physical activity and healthy eating patterns for the effective management of diabetes mellitus.